Investigating Calico Crayfish (Faxonius immunis Hagen, 1870) as a possible “sleeper” invasive species in northern Wisconsin, United States - Elle K. Sawyer; Jordan H. Hartman; Daniel K. Szydlowski; Eric R. Larson (Aquatic Invasions)
“Sleeper” invaders are non-native populations that experience time-lags post-establishment before subsequent spread or negative impacts, challenging managers to differentiate harmless non-native species from invasive species. In lakes of northern Wisconsin, United States, Rusty Crayfish (Faxonius rusticus Girard, 1852) has dominated as an invasive species for decades, but this species has recently experienced population declines. Following these F. rusticus declines, we rediscovered in 2020 a population of non-native Calico Crayfish (Faxonius immunis Hagen, 1870) that had not been documented since the 1970s. Declining F. rusticus populations may create opportunities for F. immunis spread to other lakes and impacts as a sleeper invader. We conducted additional sampling in summer 2021 that suggests F. immunis remains isolated in only one lake within this watershed. We used mitochondrial DNA barcoding to confirm these crayfish were F. immunis and had not been misidentified as a congener. Next, we investigated whether biotic interactions with F. rusticus may have prevented F. immunis spread over the past several decades. We measured agonistic behaviors using F. immunis and F. rusticus pairs in the laboratory, and then modeled differences in aggression between species while controlling for size and reproductive form. We found that F. rusticus were consistently dominant over F. immunis, suggesting that competition with an established hyper-abundant invasive species may have restricted past spread by F. immunis. Managers and policy makers should consider whether precautionary actions against F. immunis are warranted while the population of this species remains small and localized, especially in the context of F. rusticus declines.